Strengthening Competitiveness of the National Economy by Inhancing Energy Efficiency and Diversifying Energy Supply Sources in Rural Areas - GORB, Oleg; RĘBILAS, Rafał; ARANCHIY, Valentyna; YASNOLOB, Ilona; BOIKO, Stanislav; PADALKA, Viacheslav (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
The idea of inhancing competitiveness of the national economy was developed in the article from the position of improving energy efficiency and diversifying energy supply sources in rural areas, considering promising directions of development. Current situation in the country was analyzed, and comparisons with European countries were made, promising ways of sustainable rural development were determined, connected with the creation and improvement of the existing tools for using renewable energy sources. Particular attention was paid to the analysis and development of concepts of optimal models for complex utilization of renewable energy sources at the local level. Practical recommendations for introduction of renewable energy sources for energy supply in rural areas were developed. The necessity in deepening Goverment system measures to stimulate and support energy efficiency and the utilization of renewable energy sources was proven, as well as priority directions for the implementation of corresponding projects were identified. The necessity and peculiarities of the ways of diversifying energy supply sources for rural territories were studied. The concept and practical recommendations for utilization of biomass as the most promising type of renewable energy sources in rural areas of Ukraine were developed.